The language of demons and angels : Cornelius Agrippa's occult philosophy - Lehrich, Christopher I. (Brill's studies in intellectual history ;, 2003)
This work is a modern study of Agrippa's occult philosophy as a coherent part of his intellectual work. It challenges traditional interpretations of Agrippa as an intellectual dilettante, and uses modern theory and philosophy o elucidate the intricacies of his thought.